Enhancing Job Satsifaction through Workload, Knowledge Sharing Behavior, Psychological Contract and Innovative Work Behavior - Surya Safari; Febriola Hardilah; Layla Hafni; Siswoyo Siswoyo (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This research aims to determine the influence of workload, knowledge sharing behavior, psychological contract and innovative work behavior on sales consultant job satisfaction at Finance company. The population in this study were all sales consultants of the finance company, numbering 320 people. The sampling technique used was the Slovin method, the sample size for this study was 80 respondents. The data collection technique uses a questionnaire, the data analysis technique used is multiple linear regression. The results of this study show that workload has a positive but not significant effect on job satisfaction. Knowledge sharing behavior has a significant positive effect on job satisfaction. The psychological contract has a negative and significant effect on job satisfaction. Innovative work behavior has a positive but not significant effect on job satisfaction. This study suggests companies increase workload, knowledge sharing behavior, psychological contract and innovative work behavior so that sales consultant job satisfaction can increase